Usulan Kebijakan Pengendalian Persediaan Cafe X Dengan Metode EOQ - Aditya Christian Paulus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Cafe X is a business engaged in the restaurant sector. This research was conducted at Cafe X to find out the optimal inventory management policy to be applied to Cafe X. The primary data used in this study were data on the use of coffee and milk from January to December 2020 as well as data on costs associated with inventory at Cafe X. This study concludes that the total cost of inventory using the EOQ method is smaller than the total cost of inventory currently occurring at Cafe X. Based on the calculations in this study, the number of reorder points for coffee raw materials is 2,36 kg, with a safety stock as much as 0,99 kg. And the value of the reorder point for milk raw materials is 2,73 cartons, with a safety stock of 0,88 cartons. Cafe X should review the calculations yearly to take into account the reorder point and safety stock value so that the optimal value can follow the needs of Cafe X.